Evolutionary computation with intelligent systems : a multidisciplinary approach to society 5.0 - Chauhan, R. S. (Ranjit Singh) (Demystifying technologies for computational excellence : moving towards society 5.0, 2022)
"This book focuses on cutting-edge innovations and core theories, principles, and algorithms applicable to a wide area. Real-life applications, case studies, and examples are included along with emerging trends, design, and optimized solutions pivoting around the needs of Society 5.0. Evolutionary Computation with Intelligent Systems: A Multidisciplinary Approach to Society 5.0 provides a holistic view of Evolutionary Computation techniques with principles, procedures, and future applications with real-life examples. The book comprehensively explains Evolutionary Computation, design, principles, development trends, and optimization and describes how it can transform the operating context of the organization. It exemplifies the potential of Evolutionary Computation for the next generation and the role of cloud computing in shaping Society 5.0. It also provides insight into various platforms, paradigms, techniques, and tools used in diverse fields. This book appeals to all kinds of readers such as academicians, researchers, research scholars, and postgraduates"--